14 PICK YOUR THRESHOLD: A COMPARISON AMONG DIFFERENT METHODS OF ANAEROBIC THRESHOLD EVALUATION IN HEART FAILURE PROGNOSTIC ASSESSMENT. (15th December 2022) - Salvioni, Elisabetta; Mapelli, Massimo; Bonomi, Alice; Mattavelli, Irene; De Martino, Fabiana; Vignati, Carlo; Gugliandolo, Paola; Agostoni, Piergiuseppe
Abstract: Background: In clinical practice, anaerobic threshold (AT), is used to guide training and rehabilitation programs, to define risk of major thoracic or abdominal surgery, and to assess prognosis in heart failure (HF). VO2 AT has been reported as absolute value (VO2 ATabs), as percentage of predicted peak VO2 (VO2 AT%peak_pred) or as percentage of observed peak VO2 value (VO2 AT%peak_obs). A direct comparison of the prognostic power among these different ways to report AT is missing. In this work, we aim to compare the risk-identifying ability of the AT value when expressed in these three different ways in a large population of heart failure patients. This will help identify which is more correct to use in assessing patient prognosis, especially when peakVO2 is not reached appropriately. Methods: The population analyzed counts 7746 patients with heart failure with history of reduced ejection fraction (<40%), recruited between 1998 and 2020 during the MECKI score project. All patients underwent a maximal cardiopulmonary exercise test (CPET), executed in using a ramp protocol on an electronically braked cycle ergometer. Results: In this study we considered 6157HF patients with identified AT (table 1). Follow up was 4.2 years (1.9-5.0). Both VO2 ATabs population as regards prognosis (composite endpoint: cardiovascular death, urgent heart transplant or left ventricular assist device), Figure 1. Comparing AUC values, VO2 ATabs (0.680) and VO2 AT%peak_pred (0.688) performed similarly, while VO2 AT%peak_obs (0.538) was significantly weaker ( P< 0.001), Figure 2 A. Moreover, VO2 AT%peak_pred AUC value was the only performing as well as AUC based on peakVO2 (0.710), with even a higher AUC (0.637 vs. 0.618 respectively) in the group with severe HF (peakVO2 <12mL/min/kg). Finally, the combination of VO2 AT%peak_pred with Peak VO2 and VE/VCO2 shows the highest prognostic power Figure 2B. Conclusions: In HF, VO2 AT%peak_pred is the best way to report VO2 at AT in relation to prognosis, with a prognostic power comparable to that of peak VO2 and, remarkably, in severe HF patients. Fig. 1 Fig 2 Fig. 2B Table 1 Variable Mean (SD) Age (years) 61.6 (12.6) Body mass index (kg/m 2 ) 26.7 (4.4) LVEF (%) 33.0 (10.3) EDV (ml) 183 (75) ESV (ml) 126 (64) Hb (g/dl) 13.5 (1.9) MDRD (ml/min/1.73m 2 ) 72.6 (24.0) Na + (mmol/L) 139.5 (3.19) Sex (males, %) 5181 75% NYHA 1 (n, %) 1080 18% NYHA 2 (n, %) 3485 57% NYHA 3 (n, %) 1496 24% NYHA 4 (n, %) 75 1%